Corticosteroid injection of the arthritic hip: what is the indication?. Issue 1 (February 2015) - Reidy, M; Cousins, G; Finlayson, D
Forty-four patients who had image-guided corticosteroid injection of the hip were reviewed as part of a service improvement project to ascertain the medium term benefit of the procedure. Injections were indicated for treatment of hip pain or as part of a diagnostic work up to differentiate hip from back pain. At 42-month review, 39 patients fulfilled the criteria for the study. Of those having therapeutic injections, 70% had gone on to hip replacement, while only 20% of those having diagnostic injections had done so. These results suggest that, for patients who are fit for surgery, hip replacement should be the intervention of choice as corticosteroid injection does not substantially delay the need for surgery. Where there is doubt about the source of pain, there seems to be a clear role for diagnostic injection.